Languages of the World : Vietnamese - Charlotte Guillain (CHhina Raintree Publisher, 2013)
This book looks at Vietnamese, and examines where it is spoken, who speaks it, what alphabet the language is written in, and other interesting facts. The book also includes introductions on how to say key phrases in Vietnamese, such as how to say hello and goodbye, or talk about your home, school, and family. A pronunciation guide at the back of the book explains how to pronounce the Vietnamese words used throughout the book.
Keywords: Easy Read Nonfiction -- Easy Read Nonfiction